(untitled) (Medico Legal Update, 2020)
Introduction: Obsessive-compulsive disorder is an anxiety disorder in which people have recurrent, undesirable thoughts, ideas or sensations (obsessions) that make them feel compelled to go and do something (compulsion) repeatedly. Repetitive habits, such as washing hands, inspecting items or bathing, can substantially interfere with the everyday routines and social experiences of a individual. Symptoms: Behavioral changes like hyperactivity, impulsivity, repetitive movement, perfectionism and social isolation. Mood changes likes anxiety, anger and apprehension. Psychological changes like sleep disturbance, fear, repeatedly going over thoughts and narcissism. Investigation: Hb% - 13 mg/dl; Glucose plasma random – 86 mg%; Serum Globulin– 3.2gm %; serumProtein- 7gm %; HIV, HCV, HBsAg, VDRL, all of these tests were negative. Surgical Management: Patient have no past surgical history. Medical Management: Patient was treated with Ativan (Lorazepam) 3mg q6hr per oral and Therapies like Aversion therapy and Group Psychotherapy was also used. Nursing Management: Assess for physical, psychological and social data. Aware for Impact of obsessions and compulsions on physical health, mood, self-esteem and natural capacity to cope. Remember that the defense mechanisms used, the nature or structure of the feeling, the suicidal risk, the capacity to work and the space accessible for social support services. Conclusion: Patient was admitted to AVBRH and was diagnosed to have Obsessive-compulsive disorder. The got appropriate treatment and therapy and his condition has improved well.